How perceptions of the institutional environment shape organizational priorities: findings from a survey of police chiefs - Matusiak, Matthew C. (Journal of crime and justice, 2017)
A long tradition of research has examined the influence of organizational environments on criminal justice agencies. Based on survey data from a sample of local police chiefs, this study explores the effects of the institutional environment on police agency priorities. Specifically, we investigate how the perceived importance of different sectors of the institutional environment influences police agency priorities, as reported by police chiefs. The analyses reveal that certain sectors of the institutional environment exert greater influence on police organizational priorities than others. Moreover, the influence of institutional sectors differs according to the specific type of priority. Our findings reveal that institutional considerations exert more consistent effects on the importance of maintaining relationships with constituents than on maintaining law and order or adopting innovative practices. We draw on institutional theory in explaining the study’s findings.